Strategi Pemasaran Digital dan Pertumbuhan Bisnis di Era Digital: Studi Kasus pada Industri E-Commerce - Syamsuddin, Zulkifli; Semmaila, H Baharuddin; Alam, Syamsu (Program Pascasarjana STIE Amkop Makassar, 2024)
Digital marketing has become one of the key aspects in a company's business strategy in the digital era, especially in the highly dynamic e-commerce industry. This study aims to investigate the impact of digital marketing strategies on business growth in the context of the e-commerce industry. Through a qualitative approach and case study analysis, the research delves into various aspects of digital marketing strategies implemented by e-commerce companies and how it contributes to their business growth. The findings of this study provide deep insights into the effectiveness of various digital marketing techniques, such as online advertising campaigns, search engine optimization (SEO), and social media marketing, as well as how companies can integrate these strategies to achieve success in the face of fierce competition in the e-commerce market. By understanding the dynamics of digital marketing strategies in the context of the e-commerce industry, this article makes an important contribution to the understanding of the factors that influence business growth in an ever-evolving digital age. Keywords: Digital marketing, Business growth, E-commerce industry, Marketing strategy, Case study